2012
DOI: 10.7205/milmed-d-12-00151
|View full text |Cite
|
Sign up to set email alerts
|

Injuries, Changes in Fitness, and Medical Demands in Deployed National Guard Soldiers

Abstract: The predominate noncombat medical issue was musculoskeletal injury. NG Soldiers improved their body composition, strength, and endurance but experienced significant declines in aerobic fitness while deployed. These data document the association between declining aerobic fitness and increased utilization of medical resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…In the previous international military deployment study, Sharp et al [39] found that soldiers in the two highest pre-deployment aerobic fitness quartiles decreased their endurance performance during a 9-month follow-up in Afghanistan, while no changes were observed in soldiers in the initially lowest fitness quartiles. Similar findings have been reported by Warr et al [24] who found that endurance training performed at least three times a week was adequate to maintain or improve the aerobic fitness of soldiers during deployment. The previous findings support the present results, suggesting that increased endurance training frequency/volume would likely have reduced the number of soldiers with low training response.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the previous international military deployment study, Sharp et al [39] found that soldiers in the two highest pre-deployment aerobic fitness quartiles decreased their endurance performance during a 9-month follow-up in Afghanistan, while no changes were observed in soldiers in the initially lowest fitness quartiles. Similar findings have been reported by Warr et al [24] who found that endurance training performed at least three times a week was adequate to maintain or improve the aerobic fitness of soldiers during deployment. The previous findings support the present results, suggesting that increased endurance training frequency/volume would likely have reduced the number of soldiers with low training response.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to military training, only a few studies have shown that international military operations might deteriorate physical performance, especially aerobic fitness, and could induce undesirable changes in body composition, such as an increase in fat mass [22]. These changes compromise occupational performance [7,23], increase a risk of injuries [24] and thereby, have negative impact on the mission readiness of soldiers.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the importance of a broad range of physical fitness on a high level, including strength, coordination, balance, endurance, and speed, are crucial in alpine ski racing, no study was performed concerning changes in physical fitness within a season in this sport, which was investigated in rugby [12,13] or soccer players [14], among others. Additionally, a study among soldiers revealed an association between declining aerobic fitness and increased utilization of medical resources [15]. However, to the author's knowledge, the relationship between changes in physical fitness and occurrence of injuries within a season was not investigated in youth sport, yet.…”
Section: Introductionmentioning
confidence: 97%
“…Studies performed with ski racers younger than 15 years of age found the following significant injury risk factors. Athletes with weaker core flexion strength and weaker neuromuscular control were at a higher injury risk in general (10)(11)(12)(13)(14) year old athletes) [6] or had a higher risk of sustaining an ACL rupture (15)(16)(17)(18)(19) year old athletes) [8]. A decreased neuromuscular control of the knee was found to predict the risk of sustaining an ACL injury in female athletes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, maintenance of physical performance may be challenged during deployments due to increased environmental and operative demands, mental and physical stress, as well as limited access and time to train [3,4]. In fact, several studies have reported decreases in aerobic fitness after prolonged (>nine months) military deployments [5][6][7][8]. In addition, neuromuscular performance may be attenuated within a few weeks of detraining [9].…”
Section: Introductionmentioning
confidence: 99%